Agronomic Biofortification Increases Concentrations of Zinc and Storage Proteins in Cowpea Grains - Oliveira, Caroline Figueiredo; Silva, Matheus Gomes; Silva, Gutierres Nelson; Ducatti, Karina Renostro; Rocha, Maurisrael de Moura; Reis, André Rodrigues [UNESP]; Rabêlo, Flávio Henrique Silveira; Lavres, José; Santos, Elcio Ferreira (MDPI, 2024)
Zinc (Zn) is crucial for both plant metabolism and human nutrition, with its deficiency being a global health concern. Strategies to increase its availability in food, such as agronomic biofortification, have gained prominence. This study evaluated the impact of foliar spraying of Zn [at full bloom stage: 0 (control) and 600 g ha−1, as ZnSO4⋅7H2O] on the nutritional quality of cowpea (Vigna unguiculata L. Walp.) grains. Field experiments involving 20 cowpea genotypes were carried out over two seasons in a Typic Quartzipsamment under a no-tillage system. The photosynthetic responses of cowpea plants and the concentrations of Zn, amino acids, sucrose, total sugars, and storage proteins (glutelin, albumin, prolamin, and globulin) in grains were analyzed. All genotypes showed enrichment of Zn in grains in response to ZnSO4⋅7H2O application compared to untreated plants. Foliar spraying of ZnSO4⋅7H2O during initial grain filling was ideal for increasing Zn concentration in grains and improving plant physiological processes. Additionally, Zn fertilization led to higher concentrations of storage and total amino acids and proteins in the grains, supporting the rational application of Zn in cowpea production to improve the nutritional quality of grains and increase plant productivity.
Keywords: amino acids; grain quality; total sugars; Vigna unguiculata; zinc